Bio-Inspired Supramolecular Membranes: A Pathway to Separation and Purification of Emerging Pollutants. Issue 1 (2nd January 2020) - Nabeel, Faran; Rasheed, Tahir; Bilal, Muhammad; Li, Chuanlong; Yu, Chunyang; Iqbal, Hafiz M. N.
Abstract : Supramolecular membranes based separation and/or purification is an emerging technology with tunable capabilities for several applications. The proposed applications include water desalination, wastewater treatment, and separation and purification of emerging pollutants alleviating the global issue of freshwater scarcity. Advanced water purification and separation methods are required on priority to meet the demand of a growing world population. Owing to their unique physiochemical and structural properties in combination with reversible and highly selective nature, supramolecular materials are gaining research interests to engineer multifunctional separation membranes. These materials give excellent properties to the separating membranes when used with commercial crosslinked polyamide network membranes and are cost-effective from the operational viewpoint. Herein, an effort has been made to review several types of supramolecular biomimetic membranes that include pressure-driven membranes, bio-inspired supramolecular water channels, aquaporin, advanced planar aquaporin, vesicular aquaporin-based biomimetic membranes, and catecholamine-based supramolecular membranes. Several nanopore-sized materials are being developed based on aquaporin water channels, and mussel inspired catecholamines for high-performance separation membranes. This review also evaluates these technologies identifying recent progresses and commercial aspects in nanofiltration and reverse osmosis applications.